“The Money…Was Far More of a Relapse for Me”: A Qualitative Study of Women’s Experiences Transitioning from the Sex Trade to Legal Employment - Shannon K Deer (Adult Education Research Conference, 2017)
The purpose of this study was to investigate women's experiences transitioning out of the sex trade, especially related to the types and contexts of learning they employed.
Keywords: Social learning; transitional learning; sex trade